Expression analysis of cinnamoyl-CoA reductase (CCR) gene in developing seedlings of Leucaena leucocephala: A pulp yielding tree species - Srivastava, Sameer; Gupta, Ranadheer K.; Arha, Manish; Vishwakarma, Rishi K.; Rawal, Shuban K.; Kishor, P. B. Kavi; Khan, Bashir Mohammad (Plant Physiology and Biochemistry, 2011)
Removal of lignin is a major hurdle for obtaining good quality pulp. Leucaena leucocephala (subabul) is extensively used in paper industry in India; therefore, as a first step to generate transgenic plants with low lignin content, cDNA and genomic clones of CCR gene were isolated and characterized. The cDNA encoding CCR (EC 1.2.1.44) was designated as LI-CCR; the sequence analysis revealed an Open Reading Frame (ORF) of 1005 bp. Phylogenetic analysis showed that LI-CCR sequence is highly homologous to CCRs from other dicot plants. The 2992 bp genomic clone of Leucaena CCR consists of 5 exons and 4 introns. The haploid genome of L leucocephala contains two copies as revealed by DNA blot hybridization. LI-CCR gene was over-expressed in Escherichia coli, which showed a molecular mass of approximately 38 kDa. Protein blot analysis revealed that LI-CCR protein is expressed at higher levels in root and in stem, but undetectable in leaf tissues. Expression of CCR gene in Leucaena increased up to 15 d in case of roots and stem as revealed by QRT-PcR studies in 0-15 d old seedlings. ELISA based studies of extractable CCR protein corroborated with QRT-PCR data. CCR protein was immuno-cytolocalized around xylem tissue. Lignin estimation and expression studies of 5,10 and 15 d old stem and root suggest that CCR expression correlates with quantity of lignin produced, which makes it a good target for antisense down regulation for producing designer species for paper industry. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Cinnamoyl-CoA reductase; Developing seedling; Leucaena leucocephala; Lignin biosynthesis